1999
DOI: 10.1021/jf990392x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Order versus Vitrification in High-Sugar Blends of Gelatin and κ-Carrageenan

Abstract: The understanding of synthetic polymer viscoelasticity was applied to the small deformation properties of high-sugar gelatin and kappa-carrageenan mixtures. The glass transition zone in sugar/gelatin mixtures exhibited a dominant liquid-like response, which was followed by the method of reduced variables. The glass transition temperature predicted by the WLF/free volume approach coincided with the crossover of storage and loss modulus at the onset of the glassy state. The viscoelastic spectrum was resolved int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…They suggested that the aggregate formation decreased with increase in sucrose, resulting in the inhibition of aggregation. Kasapis et al. (1999) also showed that there was a considerable reduction in the values of G ′ of the gelatine–glucose composites at higher sugar concentrations.…”
Section: Effect Of Sugars On G′ During Ageingmentioning
confidence: 82%
“…They suggested that the aggregate formation decreased with increase in sucrose, resulting in the inhibition of aggregation. Kasapis et al. (1999) also showed that there was a considerable reduction in the values of G ′ of the gelatine–glucose composites at higher sugar concentrations.…”
Section: Effect Of Sugars On G′ During Ageingmentioning
confidence: 82%
“…obtained by treating a set of frequency sweeps taken at different temperatures with the WLF equation, are reproduced with an accuracy of ±2 degrees centigrade by the cooling/heating profiles of the same samples as the cross over of G and G traces passing from the glass transition region to the glassy state and, hence, are experimentally verified (Evageliou et al, 1998;Kasapis et al, 1999). The massive changes in the nature or the glassy behaviour of sugar cannot be explained on the basis of the simple mixing rule implemented by the Couchman-Karasz equation (1978) but should be the result of molecular interactions between the polymer and co-solute at high levels of solids (>70%).…”
Section: Critical Review Of Wlf/free Volume Theory 69mentioning
confidence: 65%
“…Similar transformation from free-volume derived effects in the glass transition region to the process of an energetic barrier to rotation in the solid-like environment of the glassy state was observed for high sugar/κ-carrageenan, gellan, locust bean gum and guar gum mixtures. The phenomenon appears to be universal, thus prompting us to assign physical significance to the rheological T g as the threshold of two distinct molecular processes (Evageliou et al, 1998;Sworn and Kasapis, 1998;Kasapis et al, 1999;. The temperature function in the glass transition can be compared directly with the activation energy in the glassy state using a modification of the WLF equation.…”
Section: Kasapismentioning
confidence: 99%
“…In the present study, it is hypothesized that Na + associates with the negatively charged carboxyl groups along the polymer backbone through electrostatic interactions, enhancing hydration of the gellan chains and promoting the formation of junction zones through ion–water bridges (Chandrasekaran and Radha 1995). Similarly, Kasapis and others (1999) suggested that increased levels of KCl and polymer concentration in κ‐carrageenan‐high cosolute systems offset the lack of polymer hydration, enhancing intermolecular associations to form a stronger network. In the present study, the magnitude of moduli over the complete temperature range increased with increasing Na + concentration.…”
Section: Resultsmentioning
confidence: 99%
“…At even higher levels (> 75% w/w), the mechanical spectra become strongly frequency and temperature dependent, accompanied by an apparent rise in gel strength (Nickerson and Paulson 2005). The most widely accepted theory for the spatial conformation of biopolymer chains within a high‐sugar environment (greater than approximately 75% w/w) suggests that chains organize into a weak, sparsely cross‐linked network, as was the case for gellan (Whittaker and others 1997; Kasapis 1998), gelatin (Kasapis and others 1999), and κ‐carrageenan (Evageliou and others 1998; Nickerson and Paulson 2005). …”
Section: Introductionmentioning
confidence: 99%